Game analysis of green finance assisting enterprises in carbon reduction under the participation of four parties - Wang, Jinlong; Liu, Xiangbin; Duan, Hongcheng; Wang, Lizhi (Frontiers in Public Health, 2025)
Green finance is an important measure to promote industries' green and low-carbon development, which is of great significance for achieving high-quality economic development. This article constructs a four-party evolutionary game model of “government regulatory departments, banks, non-bank financial institutions, and high-carbon enterprises,” exploring the strategic choices and evolutionary trends of the four parties in the process of green finance and promoting the green development of high-carbon enterprises. Research has shown that: (1) Government regulatory agencies should establish a sound reward and punishment mechanism. Increasing subsidies and punishment will promote the system to evolve to an ideal stable state. Still, there is a threshold for reward and punishment intensity, and its effect shows diminishing marginal benefits. (2) When banks with information advantages have a high initial willingness, they will transmit green concepts through signal effects to encourage non-bank financial institutions to actively enter the green finance market, filling the existing green credit funding supply gap and helping enterprises reduce carbon emissions. (3) The high transformation costs faced by high-carbon enterprises are still the main reason for their choice of excessive emissions. The strategic choice of enterprises mainly depends on their transformational willingness. In addition, according to the theory of willingness behavior, there is a linkage effect and mutual influence between government regulatory departments and high-carbon enterprises in their strategic choices. For the carbon reduction behavior of enterprises, whether financial institutions provide sufficient green funding support is not a determining factor, but it will also play an important role.